The Effect of Soil Coverings on Soil Respiration in Sandy Soil - Varga, Csaba (Acta Agraria Debreceniensis, 2003)
The purpose of our experiments is to study effect of different soil coverings (porous black polyethylene called agroszövet and black polyethylene) on CO2 production in sandy soil. The CO2 production was measured in our laboratory according to Witkamp (1966 cit. Szegi, 1979), after 5 days’ incubation period. Samples were taken off four times (March, May, July, September) in every year of the experiment. In May, July and September of 2000, the CO2 production was significantly higher in the control than in the treatment soil. With the exception of September, the value of CO2 production was significantly higher under black polyethylene than under agroszövet. In March and May of 2001, the soil under black polyethylene, and in July and September the control soil produced the greatest quantity of CO2. With the exception of July, significantly more CO2 was produced under black polyethylene than under agroszövet. To study the dynamic of CO2 production there was find a significantly higher value May and September of 2001 than 2000. Similarly significant higher CO2 production was detected in September than in the other months In average of two experimental years the difference between the produced CO2 under different coverings was occasionally. Explicit upward tendency in soil CO2 production was detected only in case of control soil. There was a medium (r=0,413) relationship observed between the moisture content and the CO2 producing ability of soil. To sum up the soil coverings had favourable effect on soil CO2 production very rearly, but they could help to conserve the moisture content of soil.